156k views
3 votes
Which expression is equivalent to (2x2)(3x3)(4x)2?

2 Answers

5 votes
The answer is: " 96 x⁷ " .
________________________________________________________
Step-by-step explanation:
________________________________________________________
Let us assume that the question asks to simplify the following:
________________________________________________________

→ " (2x²) (3x³) (4x)² " ;
________________________________________________________

Note that there is only ONE variable, which is "x" .
________________________________________________________
→ The expression is the same as:
________________________________________________________
→ " (2x²) * (3x³) * (4x)² " ;
________________________________________________________

→ {In other words: Note that "multiplication" of the terms is " implied ".}.
________________________________________________________

Consider the following "multiplicand" : → " (4x)² " ;
________________________________________________________

Note that: " (4x)² = (4²) * (x²) = 16x² " ;

Alternately: " (4x)² = (4 * 4) * (x²) = 16x² " ;

Alternately: " (4x)² = (4x) * (4x) = (4 * 4 * x * x) = 16x² " ;
_________________________________________________________

Now, rewrite the original expression; substituting:

→ " 16x² " ; (in lieu of the original: " (4x)² " ; as follows:
_________________________________________________________

→ " (2x²) (3x³) (16x²) " ;
_________________________________________________________

→ " (2x²) (3x³) (16x²) " ;

= " 2 * 3 * 16 * (x²) * (x³) * (x²) " ;

= " 96 * (x²) * (x³) * (x²) " ;
_________________________________________________________

→ Consider the following part of the expression:

→ " (x²) * (x³) * (x²) " ;
_________________________________________________________
Note the following property of exponents:

→ " (xª) * (xᵇ) = x⁽ª ᵇ ⁾ " ;
_________________________________________________________
As such:
_________________________________________________________

→ " (x²) * (x³) * (x²) = x⁽ ² ³ ² ⁾ = x " ;

Now, bring down the " 96 " ; and rewrite the simplified original expression;

→ which is the answer: " 96 x⁷ " .
_________________________________________________________
The answer is: " 96 x⁷ " .
_________________________________________________________
I hope this lengthy—yet detailed—explanation has been helpful to you. If it has; or if you have questions, please comment below.

Best wishes!
_________________________________________________________
User Quirimmo
by
5.4k points
3 votes

Given expression:
(2x^2)(3x^3)(4x)^2.

In order to simplify it to get an equivalent expression, we need to multiply all terms.

Let us simplify
(4x)^2 = 4^2x^2 = 16x^2

Therefore,
(2x^2)(3x^3)(4x)^2=(2x^2)(3x^3)(16x^2).


(2x^2)(3x^3)(16x^2)=2 * 3 * 16 * (x^2 * x^3 * x^2).

=
96x^(2+3+2)


96x^(7).

Therefore,
(2x^2)(3x^3)(4x)^2 is equivalent to
96x^(7).


User Alessandro Caliaro
by
6.4k points